An exceptionally flexible hydrogen-bonded organic framework with large-scale void regulation and adaptive guest accommodation abilities - Qiuyi Huang (Nature Portfolio, 2019)
Flexible hydrogen-bonded organic frameworks (FHOFs) are challenging in fabrication but promising materials for applications in separation and sensing. Here, the authors report a stimuli responsive and flexible HOF which can adapt to different guests by regulating the molecular conformation.